The efficiency of Jordan insurance companies and its determinants using DEA, slacks, and logit models - Jaloudi, Mutasem Mahmoud (University of Economics Ho Chi Minh City, 2023)
Purpose The purpose of this paper is to evaluate the technical efficiency in the Jordan insurance market and examine the internal and external determinants that appear to affect the technical efficiency of the insurance companies. Design/methodology/approach The study used panel data for 22 insurance companies operating inside Jordan over the period 2000–2016. The author used the data envelopment analysis to evaluate the technical efficiency scores, slacks-based and logit models to examine the efficiency determinants. Findings The study found that there is a slight development of technical efficiency for the Jordanian insurance companies during the study period. In addition, there is a substantial efficiency difference among insurance companies each year, and there is a variation at the level of efficiency for each company in each year. The results also showed that owners’ equities are among the most important internal determinants of companies’ efficiency, and there is a significant correlation between type, size and return on assets of the insurer and its efficiency. Originality/value This study provides insurance management with relevant indicators that would guide them to make efficient use of the resource base. The period of study also covers the period following the adoption of the insurance law and the issuance of most of the legislation related to the work of insurance companies.